Determinan Pendapatan Petani Kopi Di Kabupaten Bangli - Sutawibawa, Ade Rama; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
One of the plantation products exported by Indonesia is coffee, which is known as one of the main sources of state income and is a plantation product which is a high economic value global commodity. This study aims to 1) analyze the direct influence of capital, labor and work experience on production, 2) analyze the direct influence of capital, labor, work experience and production on income and 3) analyze and explain the role of production in mediating the influence of capital, labor and work experience on the income of coffee farmers in Bangli Regency. The data used in this study are primary data obtained by distributing questionnaires to 97 coffee farmers in Bangli Regency. The analysis technique used in this study is path analysis. The test results aimed at capital, labor and work experience have a positive and significant effect on coffee production in Bangli Regency. Capital, labor, work experience and production have a positive and significant effect on the income of coffee farmers in Bangli Regency. Production mediates the influence of capital, labor, and work experience on the income of coffee farmers in Bangli Regency.